Canonical correlation analysis of laying, growth and blood biochemical traits of Shaoxing Duck - CHEN Hai-yan; LÜ Hong; ZHU Hai-ping; FU Yan; LU Li-zhi (浙江大学学报. 农业与生命科学版)
Canonical correlation analysis of three sets of variables including nine traits of Shaoxing Duck was performed. The results showed that the first canonical correlation coefficients between laying performance and growth rate (0.8422), as well as between the growth rate and blood biochemical traits (0.4149), were highly significant. They constituted 99.23% and 90.86% of total correlation respectively. The first canonical correlation coefficient between the laying performance and the blood biochemical traits was estimated (0.4369) significantly and expressed 97.99% of the total correlation. The analysis indicated that main traits for the canonical correlation coefficients were average egg weight, body weight at 30 days, body weight at 60 days and the activity of Glutamat-Pyruvat-Transferase (GPT) at 60 days. The results of the analysis will have certain significance for early selection of Shaoxing Duck using the growth rate and the blood biochemical traits.